(untitled) (Tempo e Argumento, 2024)
This article deals with writings by ordinary prisoners in the 20th century. The first part of the text discusses how these sources can be used to think about the different layers that make up institutional practices, making it possible to broaden our view of the history of prisons. The analysis goes through the disputes over memory that are intertwinedwith the binary dichotomy of “political prisoners” and “ordinary prisoners”. Finally, the article explores how research, based on these sources, can have its results transmuted into products that aim to reach a wider audience, focusing on the process of creating podcasts based on lives traversed by institutional experience. The proposal takes the history of prisons as a moving and unavoidable theme for the history of the present time.